(untitled) (Konturen, 2026)
Chicken Little is the natural heir to Kafka’s feckless Country Doctor. The impossible conditions that expose the physician as a quack prepare Chicken Little’s coop-mates in 1943 to buy into the Big Lie, i.e. the sky is falling. The falsehood is not what it appears. The sky is not falling because, as Kafka demonstrates, it has already fallen. Nothing is where it should be, all sign systems mislead or lead nowhere, and so-called healers only bring Unheil or disaster. As Disney’s 1943 short emphasizes, the country doctor easily metamorphoses into the authoritarian leader using the Big Lie to lead the masses to their death.